The Influence of Self-Efficacy and Social Support on Adolescent Self-Adjustment in Islamic Boarding Schools - Tanjung Silain, Demas; Harahap, Farida; Aziz Mursy, Abdul; Malisa, Malisa (Devotion : Journal of Research and Community Service, 2024)
This research aims to explain the impact of self-efficacy and social support on the adjustment of new female students at the Darul Qur'an Wal-Hadist Sekotong Islamic Boarding School. The method used was quantitative research with an ex-post facto approach, and the sample consisted of 100 new students from various levels of education (SMP, SMA, MA, and SMK) at the Darul Qur'an Wal-Hadist Sekotong Islamic Boarding School Foundation. Data collection was carried out using a questionnaire using three Likert scales, namely the self-efficacy scale, social support, and adjustment. Data analysis was carried out using simple linear regression techniques. The research results show the following findings: First, self-efficacy has a significant effect on the adjustment of new students and female students, as shown by a significance of 0.000. This shows that the level of self-confidence of students in overcoming the challenges and burdens of Islamic boarding schools has a positive impact on their ability to adapt. Second, social support also has a significant influence on adjustment, with a significance of 0.035. Support from the surrounding environment, both from fellow students and teachers, plays an important role in helping students adapt to the new Islamic boarding school environment. Third, there is a significant influence between self-efficacy and social support on the adjustment of new students and female students at the Darul Qur'an Wal-Hadist Sekotong Islamic Boarding School. These results indicate that internal (self-efficacy) and external (social support) factors together have a positive impact on the adjustment abilities of new students. This research makes an important contribution to understanding the factors that influence the adjustment of new santri and female students in the Islamic boarding school context, with potential implications for the development of support and coaching programs for those new to the Islamic boarding school environment.